2021
DOI: 10.1007/s00270-021-02956-5
|View full text |Cite
|
Sign up to set email alerts
|

Computational Fluid Dynamics Modeling of Liver Radioembolization: A Review

Abstract: Yttrium-90 radioembolization (RE) is a widely used transcatheter intraarterial therapy for patients with unresectable liver cancer. In the last decade, computer simulations of hepatic artery hemodynamics during RE have been performed with the aim of better understanding and improving the therapy. In this review, we introduce the concept of computational fluid dynamics (CFD) modeling with a clinical perspective and we review the CFD models used to study RE from the fluid mechanics point of view. Finally, we sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Indeed, recent studies have shown that even highly simplified simulations of the transport of microspheres through a realistic hepatic vascular tree can result in biodistributions that correspond well with empirical data, corroborating this link between the properties of the vasculature, the resulting blood flow dynamics and microsphere deposition. [26][27][28][29][30] Although the posttreatment effects of radioembolization on tumor perfusion have been established before, 28 the potential for a direct link between pretreatment perfusion and posttreatment tumor absorbed dose, as proposed in this study, has not.…”
Section: Discussionmentioning
confidence: 81%
“…Indeed, recent studies have shown that even highly simplified simulations of the transport of microspheres through a realistic hepatic vascular tree can result in biodistributions that correspond well with empirical data, corroborating this link between the properties of the vasculature, the resulting blood flow dynamics and microsphere deposition. [26][27][28][29][30] Although the posttreatment effects of radioembolization on tumor perfusion have been established before, 28 the potential for a direct link between pretreatment perfusion and posttreatment tumor absorbed dose, as proposed in this study, has not.…”
Section: Discussionmentioning
confidence: 81%
“…If release maps similar to CPRGs need to be obtained, CFD simulations can be used to generate the flow pathlines after planar injection, as shown by Taebi et al (2021) . To estimate only the particle distribution, the CFD simulation would not even be needed, reducing the simulation time to 0 ( Aramburu et al, 2022 ). However, it should also be emphasized that the particles in this study are small, and that fluid-particle differences may increase for larger particles (i.e., for TACE).…”
Section: Discussionmentioning
confidence: 99%
“…Hemodynamics can be studied using computational fluid dynamics (CFD) [ 26 ], and recent developments in computers and medical imaging software have made the CFD analysis of blood flow both reliable and accessible to clinicians. CFD has been applied to analyze various vascular diseases, such as coronary artery disease [ 27 ], aortic dissection [ 19 , 28 , 29 ], liver radioembolization [ 30 ], and intracranial aneurysm [ 31 ].…”
Section: Introductionmentioning
confidence: 99%